Systems medicine and proactive P4 medicine: revolutionizing healthcare. Predictive, preventive, personalized and participatory - Hood, Lee (Henry Stewart Talks, 2014)
Systems Medicine and Proactive P4 Medicine, Systems medicine has reached a tipping point, Blood is window to distinguishing health from disease, Large-scale, multiparameter, digital-age, longitudinal, Framingham-like clinical trials that will transform medicine, Transitions from health to disease and back will give fundamental insight into early origins of disease